IPMS experiences with Tef value chain development in Ethiopia - Shiferaw, A. (International Livestock Research Institute, 2011)
Abebe Shiferaw discusses how the IPMS project at ILRI used the value chain approach to help Teff producers become more competitive. He was speaking at the IPMS experience-sharing workshop on Market-Oriented Smallholder Development in Ethiopia, 2-3 June 2011 in Addis Ababa.